Tingkat Profesioanlisme Aparatur Kecamatan dalam Pelayanan Publik: Studi Kasus di Kecamatan Bangun Purba - Aulia Trimahua, Kiki; Rahmah, Sitti (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to evaluate the level of professionalism of government officials in public services at the Bangun Purba Sub-District Office, Rokan Hulu Regency. The research method employs a qualitative descriptive approach, utilizing a case study. Data were collected through in-depth interviews, direct observation, and documentation. Informants consisted of sub-district heads, section heads, staff, and service user communities. The analysis refers to Martin Jr.'s theory, as presented in Thoha (2001), which includes five indicators: proficiency, readiness, responsibility, discipline, and attitude. The results showed that although most ASNs demonstrated good attitudes and commitment, there were still significant shortcomings in aspects such as proficiency, readiness, and discipline, especially among honorary staff. The implications of this study encourage local governments to develop policies that increase the capacity of their apparatus through continuous training and a performance evaluation system based on professional indicators, as well as expanding opportunities for honorary personnel in competency development.